ASSA13-13-8 The Study of Improvement Hydration in Preventing Contrast Induced. (29th April 2013) - Yong, Xia; Wen-juan, Liu; Ying, Shen
Abstract : Background: Contrast-induced nephropathy (CIN) is the third most common cause of hospital acquired acute kidney injury. Hydration is the used of the early and widely accepted and effective method to reduce CIN. However, the hydration is easily to cause heart failure because of volume overload. REMEDIAL II study indicates that the Renal Guard System significantly reduced the incidence of CIN for patients at high- risk in 2011. Brar SS's study receiving hydration in 3 h adjusting the infusion volume with LVEDP significantly reduced CIN in 2012. However, these two new methods require special equipment, having traumatic, not suitable for a large number of patients simultaneously. Objective: To research the effect of the improvement hydration that accomplished through a variety of measures in preventing CIN and protection of heart function. Methods: Total 160 patients receiving CAG and/or PCI and belonging to medium- and high-risk according to the CIN risk score were recruited and divided into two groups. One group was routine hydration (control group, n = 80) and another group was calculated the amount of fluid as urine output (improvement group, n = 80). All patients in the two groups receive hydration with 0.9%NaCl continued 24 hour's time, the speed was 1.5ml/kg·h in the control group, but in the improvement group maintain the patient's blood volume dynamic equilibrium according to adjustment the fluid volume and speed by the urine volume, recessive loss, blood pressure, heart rate and peripheral venous pressure. The postoperative 24 h fluid intake and output volume, heart function index (NT-proBNP), renal function index (Scr, BUN) at postoperative 24h, 48h, 72h and the urinary NGAL at postoperative 2h, 4h, 6h, 12h, 24h, 48h, 72h were collected and analysed. Results: ➀ The postoperative 24 h infusion volume and urine volume in the improvement group were significantly higher than that in the control group ( P < 0.01=. the incidence of CIN in the improvement group was significantly lower than that in the control group ( P < 0.05=. ➁ The heart function in the improvement group after CAG and/or PCI was better than that in the control group ( P < 0.05). ➂ The time in hospital and the rate of adverse reaction during hospitalisation were no significant difference between the two groups ( P > 0.05). Conclusions: The improvement hydration can reduce the incidence of CIN and protect heart function by continuous maintaining the balance of patient's blood volume.